Delay from symptom onset to treatment start among tuberculosis patients in England, 2012–2015. Issue 12 (20th June 2018) - Loutet, M. G.; Sinclair, C.; Whitehead, N.; Cosgrove, C.; Lalor, M. K.; Thomas, H. L.
Abstract: Improving access to tuberculosis (TB) care and ensuring early diagnosis are two major aims of the WHO End TB strategy and the Collaborative TB Strategy for England. This study describes risk factors associated with diagnostic delay among TB cases in England. We conducted a retrospective cohort study of TB cases notified to the Enhanced TB Surveillance System in England between 2012 and 2015. Diagnostic delay was defined as more than 4 months between symptom onset and treatment start date. Multivariable logistic regression was used to identify demographic and clinical factors associated with diagnostic delay. Between 2012 and 2015, 22 422 TB cases were notified in England and included in the study. A third (7612) of TB cases had a diagnostic delay of more than 4 months. Being female, aged 45 years and older, residing outside of London and having extra-pulmonary TB disease were significantly associated with a diagnostic delay in the multivariable model (aOR = 1.2, 1.2, 1.2, 1.3, 1.8, respectively). This study identifies demographic and clinical factors associated with diagnostic delay, which will inform targeted interventions to improve access to care and early diagnosis among these groups, with the ultimate aim of helping reduce transmission and improve treatment outcomes for TB cases in England.